2016
DOI: 10.24925/turjaf.v4i9.782-786.745
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dairy Management on Milk Quality Characteristics

Abstract: The article focuses on the impact of different dairy management types on quality characteristics of organic and conventional milk. The study was conducted during 9 months (spring-autumn), raw milk samples were collected from organic and conventional dairy farms from two Ukrainian regions. The milk samples were analyzed for dry matter, total protein and non-protein nitrogen, ammonia content and values of stable isotopes 13С/12С were measured in fat and milk protein fractions. The values of dry matter, total pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…A low udder pressure will then increase the milk secretion in the udder and resulted in better milk quality. Petrov et al (2016) stated that different dairy farms management will produce different milk quality. Their research in Turkey showed that organic dairy farming management produced milk with higher protein compared to the conventional farm management.…”
Section: Results and Discussion Milk Quality From Different Dairy Farmsmentioning
confidence: 99%
“…A low udder pressure will then increase the milk secretion in the udder and resulted in better milk quality. Petrov et al (2016) stated that different dairy farms management will produce different milk quality. Their research in Turkey showed that organic dairy farming management produced milk with higher protein compared to the conventional farm management.…”
Section: Results and Discussion Milk Quality From Different Dairy Farmsmentioning
confidence: 99%
“…While there is an assumption that the percent of plant with C 4 -photosynthesis type in the cattle diet have a more pronounced effect on the fat fraction (Molkentin and Giesemann, 2010), however, the effect on protein fraction could also be essential (Petrov et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned, that δ 13 C threshold of -26.5‰, which could be applicable to German organic dairy was not spread for products from other countries (Molkentin, 2013). Previous study in Ukraine has shown that the average values of δ 13 C fat in organic milk (-26.00‰) were significantly lower than in conventional (-23.14‰) (Petrov et al, 2016), that could be explained by a different amount of maize in cattle diet.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations